Influence of Electrode Shape and Spacing on Corona Discharge Phenomena using a Plasma Generator - Jefri Dharmesta; Salma Aulia Rohimah; Yudan Whulanza; Ario Sunar Baskoro (Department of Physics, Sebelas Maret University, 2025)
Electrical discharges that happen near high-voltage conductors are known as corona discharges. It will produce light and sound as it ionises the surrounding air. The purpose of this work is to investigate how conductor form and spacing affect the properties of corona discharge produced by a plasma generator. In this study, conductor shapes such as triangle, W-shaped wire, syringe (point), and L-shaped wire (horizontal) were experimented with, as well as the distance between conductors. The outcome demonstrates that conductor spacing affects the corona discharge's plasma intensity, with shorter distances producing stronger electric fields and greater discharge intensities. Furthermore, the dispersion of the plasma is greatly influenced by the conductor's shape, since every conductor shape results in a different pattern of plasma distribution. These findings offer important new information for the development and improvement of systems that make use of corona discharge events.